Pluralisme Islami “ Menelusuri dan Mengaktualisasikan Konsep La Convivencia di atas Pentas Global - Saidul Amin (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
When the veil and hijjab in one hemisphere to the other hemisphere has been revealed, then every religion and ideology appear transparent on the one stage of civilization. This pluralism sometimes not capable of biting but rarely have to compete. Then the concept of what Islam has to offer in creating community harmony pluralism to remain living in harmony and work together to build civilization. Perhaps now is the time to look back, to medieval times, when convivencia form and become the model of Islamic pluralism